Responding to unexpected infant deaths: experience in one English region. Issue 4 (29th November 2009) - Sidebotham, Peter; Blair, Peter S; Evason-Coombe, Carol; Edmond, Margaret; Heckstall-Smith, Ellen; Fleming, Peter
Abstract : Aim: New national procedures for responding to the unexpected death of a child in England require a joint agency approach to investigate each death and support the bereaved family. As part of a wider population-based study of sudden unexpected deaths in infancy (SUDI) we evaluated the implementation of this approach. Methods: A process evaluation was carried out using a population-based study of all unexpected deaths from birth to 2 years in the South West of England between January 2003 and December 2006. Local police and health professionals followed a standardised approach to the investigation of each death, supported by the research team set up to facilitate this joint approach as well as collect data for a wider research project. Results: We were notified of 155/157 SUDI, with a median time to notification of 2 h. Initial multi-agency discussions took place in 93.5% of cases. A joint home visit by police officers with health professionals was carried out in 117 cases, 75% within 24 h of the death. Time to notification and interview reduced during the 4 years of the study. Autopsies were conducted on all cases, the median time to autopsy being 3 days. At the conclusion of the investigation, a local multi-agency case discussion was held in 88% of cases. The median time for the whole process (including family support) was 5 months. Conclusions: This study has demonstrated that with appropriate protocols and support, the joint agency approach to the investigation of unexpected infant deaths can be successfully implemented.